Non-problem gamblers show the same cognitive distortions while playing slot machines as problem gamblers, with no loss of control and reduced reality control, though – An experimental study on gambling - Krébesz, Róbert; Ötvös, Dóra Kata; Fekete, Zita (Frontiers in Psychology, 2023)
Background: Cognitive distortions can result in maladaptive interpretations of events and maladaptive behavior. In the case of gambling, such distortions can contribute to the maintenance of the disorder. Our current research aimed to conduct an experiment to possibly detect cognitive biases characteristic of persons with gambling addiction in a non-gambling sample of the general population, and to study the effect of "big win" on cognitive distortions. Methods: A specifically designed and preprogrammed slot machine simulation was carried out, with 90 rounds split into 3 sections. During the simulation every participant verbalized their thoughts and feelings; the verbalizations were recorded. Then a content analysis was conducted to search for indications of cognitive distortions. The sample was separated into two experimental groups: one of the groups experienced the "big wins" in the first section, while the other group had them in the second section of the experiment. Results: Content analysis revealed numerous cognitive biases. Cognitive distortions usually present in problem gambling were detected in our sample from the general population as well. However, we could not distinguish cognitive biases indicating serious loss of control, or distortion of reality control. A further finding is that early losses provoke the emergence of more cognitive distortions, while early big win leads to more intense loss-chasing in the later stages of gambling. Conclusions: The appearance of reality-checking uncertainty or loss of control can be alarming for the development of gambling. Losses and big wins can provoke different cognitive distortions, encouraging the person into further gambling behavior.